Evidence of character displacement in microhabitat use between two tropical sympatric Holcosus lizard species (Reptilia, Teiidae) - F. Ruiz Real; J. Martín (Animal Biodiversity and Conservation)
Interspecific competition between sympatric related species leading to character displacement is critical for species coexistence, especially in tropical habitats. We examined microhabitat use of two sympatric species of tropical lizards of the genus Holcosus in relationship to the microhabitats available in two ecosystems. The species H. festivus lives exclusively in the forest and uses microhabitats in proportion to their availability; while the other, H. quadrilineatus, lives both in forest and on the beach and selects microhabitats with specific characteristics. In the ecosystem where these two lizards live in sympatry (forest), we observed a differential microhabitat use between the two species. However, these differences indicated changes in habitat use by H. quadrilineatus (the smaller species) concerning its patterns of habitat selection in the ecosystem (beach) where only this species occurs. The age of the lizards did not affect the patterns of selection of microhabitats of either species. Shifts in microhabitat use may allow coexistence in sympatry of both species, which might result from the competitive exclusion of the smaller species by the larger species.